THE RELIABILITY OF THE BOLTON RATIO WHEN APPLIED TO THE INDONESIAN POPULATION - Kusnoto, Joko (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The objective of this study is to determine whether Bolton ratio can be applied clinically to the Indonesian population and to determine a more suitable Bolton ratio for the Indonesian population. Methods: This study was conducted on 120 readily available study models of treated cases comprising 37 males and 83 females. Two investigators separately measured the mesiodistal crown width of maxillary and mandibular tooth on each study model using sliding calipers. According to Bolton's method, the overall and anterior ratios from each sample were calculated and the mean was generated. Using Student's t-test with a 95% confidence interval, the investigators compared whether there is a significant difference between the ratio from Bolton's samples and the ratio from the Indonesian samples. Results: The result of this study showed that, for Indonesian samples, the overall ratio is 89.7±2.05, while the anterior ratio is 76.4±2.76. Student's t-test showed that there is a statistically significant difference (p<0.05) between the results of this study and that of Bolton's study for both the anterior and overall ratios. Conclusion: It can be concluded that there is a difference between Indonesian population and Caucasian population in tooth size and Bolton ratio value. Therefore, original Bolton ratio value cannot be used as an accurate diagnostic tool for Indonesian population.